Fibroblast growth factor 13-mediated regulation of medium spiny neuron excitability and cocaine self-administration - Dvorak, Nolan M.; Di Re, Jessica; Vasquez, Tileena E. S.; Marosi, Mate; Shah, Poonam; Contreras, Yorkiris M. Mármol; Bernabucci, Matteo; Singh, Aditya K.; Stallone, Jariatu; Green, Thomas A.; Laezza, Fernanda (Frontiers in Neuroscience, 2023)
Cocaine use disorder (CUD) is a prevalent neuropsychiatric disorder with few existing treatments. Thus, there is an unmet need for the identification of new pharmacological targets for CUD. Previous studies using environmental enrichment versus isolation paradigms have found that the latter induces increased cocaine self-administration with correlative increases in the excitability of medium spiny neurons (MSN) of the nucleus accumbens shell (NAcSh). Expanding upon these findings, we sought in the present investigation to elucidate molecular determinants of these phenomena. To that end, we first employed a secondary transcriptomic analysis and found that cocaine self-administration differentially regulates mRNA for fibroblast growth factor 13 (FGF13), which codes for a prominent auxiliary protein of the voltage-gated Na + (Nav) channel, in the NAcSh of environmentally enriched rats (i.e. resilient behavioral phenotype) compared to environmentally isolated rats (susceptible phenotype). Based upon this finding, we used in vivo genetic silencing to study the causal functional and behavioral consequences of knocking down FGF13 in the NAcSh. Functional studies revealed that knockdown of FGF13 in the NAcSh augmented excitability of MSNs by increasing the activity of Nav channels. These electrophysiological changes were concomitant with a decrease in cocaine demand elasticity (i.e., susceptible phenotype). Taken together, these data support FGF13 as being protective against cocaine self-administration, which positions it well as a pharmacological target for CUD.